The first word in accessibility is "access". - Regan, Patrick (AAC: Augmentative & Alternative Communication, 2025)
This paper focuses on access challenges that I have experienced as someone who uses AAC, how my team and I have resolved them, and what challenges I face now. I use AAC and assistive technology (AT) to work, advocate, exercise, socialize, manage my healthcare, and participate in community-based activities. Over the years, I have used many different AAC systems, computer applications, and access methods as technology advanced and my needs and skills changed because of spinal muscular atrophy. Too often AAC is only considered as a speech prosthesis, rather than as a support for communication in all its forms to enhance participation in society. People with disabilities need access to functional communication, including not just speech generating devices, but also the Internet, phone, computers, and software for medical and health reasons as well as education, employment, and community participation. Researchers need to learn more about the challenges that AAC users face and how our access needs change over time. My hope is that they will develop a new generation of AT that will make it possible to integrate all my access methods so that I can use them in a wide range of positions and for a multitude of purposes.